Regulatory T Cell Metabolism in the Hepatic Microenvironment - Wawman, Rebecca Ellen; Bartlett, Helen; Oo, Ye Htun (Frontiers in Immunology, 2018)
Thymic-derived naturally occurring regulatory T cells (tTreg) are crucial for maintaining peripheral immune homeostasis. They play a crucial role in preventing autoimmunity and maintaining organ transplant without requiring immunosuppression. Cellular metabolism has recently emerged as an important regulator of adaptive immune cell balance between Treg and effector T cells. While the metabolic requirements of conventional T cells are increasingly understood, the role of Treg cellular metabolism is less clear. The continuous exposure of metabolites and nutrients to the human liver via the portal blood flow influences the lineage fitness, function, proliferation, migration and survival of Treg cells. As cellular metabolism has an impact on its function, it is crucial to understand the metabolic pathways wiring in regulatory T cells. Currently, there are ongoing early phase clinical trials with polyclonal and antigen-specific good manufacturing practice (GMP) Treg therapy to treat autoimmune diseases and organ transplantation. Thus, enhancing immuno-metabolic pathways of Treg cells by translational approach with existing or new drugs would utilize Treg cells to their full potential for effective cellular therapy.